Aktivitas Antioksidan Kombinasi Madu Monoflora dengan Ekstrak Daun Namnam (Cynometra cauliflora L.) - La Ode Sumarlin; Melina Hadera; Sri Yadial Chalid; Dede Sukandar (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2018)
Honey and namnam leaves (Cynometra cauliflora L.) have been shown to have antioxidant activity. Combination of both materials potent to be used as functional food. In this study, antioxidant activity of samples was measured by the DPPH method (1,1-diphenyl-2-picrylhydrazyl) (IC50) while total phenolic, total flavonoids, and vitamin C were determinated by UV-Vis spectrophotometry. Honey samples used were commercial packaging rambutan honey (MR), commercial packaging rubber honey (MK), and commercial unpackaging rambutan honey (MR2). The combination ratio of honey and namnam leaves extract was 1:1, 1:2 and 2:1 (b/b). The highest value of total phenolic, total flavonoids, vitamin C and antioxidant activity in namnam leaves extract (N) was 267.690 mg GAE/g, 12.284 mg QE/g, 203.500 mg AA/g and IC50 0.004 mg/mL, respectively. The highest value of total phenolic was 0.588 mg GAE/g in MR2, while the highest value of total flavonoids and antioxidant activity (IC50) were 0.027 mg QE/g and 21.576 mg/mL in in MR, respectively. Combination MR and MR2 with namnam leaves extract (MR-N and MR2-N) with ratio 1:2 gave the highest antioxidant activity with IC50 value 0.005±0.000 mg/mL in both samples. The highest value of total phenolic, total flavonoid, and vitamin C in MR-N and MR2-N was 266.027 mg GAE/g, 9.790 mg QE/g, and 100.33 mg AA/g, respectively. Therefore, the combination is potential as a functional food Madu dan daun namnam (Cynometra cauliflora) telah terbukti memiliki aktivitas antioksidan. Kombinasi kedua bahan ini akan sangat potensial digunakan sebagai pangan fungsional. Pada penelitian ini, antioksidan diukur dengan metode DPPH (1,1-difenil-2-pikrilhidrazil) (IC50), sedangkan total fenolik, total flavonoid, vitamin C menggunakan spektrofotometer UV-Vis. Sampel madu yang digunakan adalah madu rambutan kemasan komersial (MR), madu karet kemasan komersial (MK), dan madu rambutan tanpa kemasan komersial (MR2). Perbandingan kombinasi madu dan ekstrak daun namnam masing-masing 1:1, 1:2 dan 2:1 (b/b). Hasil analisis menunjukkan bahwa total fenolik, total flavonoid, vitamin C dan aktivitas antioksidan tertinggi terdapat pada ekstrak daun namnam (N) masing-masing sebesar 267,690 mg GAE/g, 12,284 mg QE/g, 203,500 mg AA/g dan IC50 0,004 mg/mL. Kandungan total fenolik tertinggi pada sampel madu adalah MR2 sebesar 0,588 mg GAE/g, sedangkan total flavonoid dan aktivitas antioksidan tertinggi pada MR yaitu 0,027 mg QE/g dan IC50 21,576 mg/mL. Sampel MR dan MR2 kombinasi dengan ekstrak daun namnam (MR-N dan MR2-N) dengan perbandingan 1:2 memberikan aktivitas antioksidan tertinggi dengan nilai IC50 sebesar 0,005 ± 0,000 mg/mL. Total fenolik, total flavonoid, dan vitamin C tertinggi pada kombinasi MR-N dan MR2-N masing-masing sebesar 266,027 mg GAE/g, 9,790 mg QE/g, dan 100,33 mg AA/g. Oleh karena itu, kombinasi tersebut potensial sebagai pangan fungsional